2021
DOI: 10.1021/acs.analchem.1c02403
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Electrochemiluminescence Efficiency Quantification Strategy Exemplified with Ru(bpy)32+ in the Annihilation Pathway

Abstract: This work presents a thorough guide to procedures for absolute electrochemiluminescence (ECL) quantum efficiency (ΦECL) measurements, which if employed effectively should raise the research impact of ECL studies for any luminophore. Absolute measurements are not currently employed in ECL research. Instead, ECL efficiencies have been determined relative to Ru­(bpy)3 2+ under similar conditions, regardless of whether the conditions are favorable for Ru­(bpy)3 2+ emissions or not. In fact, the most cited Ru­(bpy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 44 publications
5
57
1
Order By: Relevance
“…These devices were powered through these contacts by a Keithley 2400 Source meter (Solon, OH) controlled by a computer via a NI (Austin, TX) GPIB‐USB cable. Device emission was collected by a Hamamatsu Photonics R3896 photomultiplier tube (Japan) held at −750 V by a high voltage power supply (Newport Technology Inc., Irvine, CA), which corresponded to a gain factor of 1.3x10 6 [19] . The photomultiplier tube (PMT) response was input into a Keithley Model 6487 picoammeter (Solon, OH) held at an appropriate sensitivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These devices were powered through these contacts by a Keithley 2400 Source meter (Solon, OH) controlled by a computer via a NI (Austin, TX) GPIB‐USB cable. Device emission was collected by a Hamamatsu Photonics R3896 photomultiplier tube (Japan) held at −750 V by a high voltage power supply (Newport Technology Inc., Irvine, CA), which corresponded to a gain factor of 1.3x10 6 [19] . The photomultiplier tube (PMT) response was input into a Keithley Model 6487 picoammeter (Solon, OH) held at an appropriate sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Both the voltage application from Keithley 2400 and the PMT signal were controlled and acquired simultaneously using a custom designed 2019 LabVIEW (Austin, TX) code. Luminance‐current‐voltage data transformations were performed according to our previous reports [19–20] . Briefly, photocurrent in nA measured from the PMT was transformed to luminance in cd/m 2 using three other measured values: a background‐subtracted, normalized GQD LEC emission spectrum, a precisely measured, calibrated experimental setup and the photopic luminous efficiency function representing the visual sensitivity of the human eye to light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is unlikely that the PMT would get more than two events in the duration, owing to the following reasons: (i) it has been shown that only 5.5% of incoming photons can be effectively converted to photoelectron signals by our R928 PMT during our absolute efficiency calibration, ESI Section 6 and Fig. S8–S19 † ; 45 (ii) spherical ECL emission is proven to be detected for a substantial small part upon examination of our detection system for the absolute ECL quantum efficiency; 45 (iii) Au 38 nanocluster ECL emissions occur at 930 nm, which is almost at the wavelength detection limit of our PMT response curve. 38,45 …”
mentioning
confidence: 99%
“…ECL efficiency (Q ECL ) of Au 18 0 /TPrA systems was determined relative to that of the Ru(bpy) 3 2 + /TPrA by determining the ratios of integrating the accumulated ECL spectrum to electrochemical charge for both systems and then calculating the fraction of the formal over the latter (for ECL efficiency calculation details, see Section 7 in the Supporting Information). [18] Figure 2. Spooling ECL spectroscopy of 0.1 mM Au 18 0 with 6 mM TPrA.…”
mentioning
confidence: 99%